PENINGKATAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN PENDEKATAN SAINTIFIK - Anjaswari, Puji; Slameto, Slameto (TAMAN CENDEKIA: Jurnal Pendidikan Ke-SD-an, 2018)
Along with the advancement and the changing of times, the quality of learning process becomes a demand that must be achieved.The learning process implemented should be student centred so as to improve the quality of education. In order to achieve meaningful learning process, the scientific approach is appliedso that the learners can find their own concepts in learning by the guidance of theirteacher. The teacher only holds a role as a facilitator in learning. Along with the spiritof the governmentin applying the scientific approach in the 2013 curriculum, it is still questionable whetherthe scientific approach implementation will have an impact on improving learning outcomes or not. The documents of previous studies are used in this study. The data collection is obtained through google scholar by browsing the electronic journals. From the search results obtained, 10 research journals areanalysed further in the form of percentage (%). Based on the results of the analysis, the scientific approach is able to improve learning outcomes, ranging from the lowest 2% to the highest 34,51% with an average of 23,35%.